Report on 1995 Grenada agricultural census (The Unit St. George'sGD, 1996)
Provides information on the objectives, definitions, methodology and main activities of the 1995 Grenada Agricultural Census (GAC), as well as a brief analysis of the 1995 GAC data. Presents the most important tables containing the raw final results at national and parish level, some tables at watershed level are also included.
Located in the Statistics Section